CFD investigation of flow in and around a natural draft cooling tower - Storm, Heinrich Claude (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.